2008
DOI: 10.1142/s0219720008003813
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitous Reassortments in Influenza a Viruses

Abstract: The influenza A virus is a negative-stranded RNA virus composed of eight segmented RNA molecules, including polymerases (PB2, PB1, PA), hemagglutinin (HA), nucleoprotein (NP), neuraminidase (NA), matrix protein (MP), and nonstructure gene (NS). The influenza A viruses are notorious for rapid mutations, frequent reassortments, and possible recombinations. Among these evolutionary events, reassortments refer to exchanges of discrete RNA segments between co-infected influenza viruses, and they have facilitated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Serological test demonstrated that at least 56 subtypes (67.46%) exchanged their fragments with another subtype among 83 subtypes of influenza A viruses [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serological test demonstrated that at least 56 subtypes (67.46%) exchanged their fragments with another subtype among 83 subtypes of influenza A viruses [5].…”
Section: Discussionmentioning
confidence: 99%
“…This question is important because the reassortment particularly facilitates the generation of pandemic and epidemic strains, which led to the pandemics in 1957 *Address correspondence to this author at the State Key Laboratory of Nonfood Biomass Enzyme Technology, National Engineering Research Center for Non-food Biorefinery, Guangxi Key Laboratory of Biorefinery, Guangxi Academy of Sciences, 98 Daling Road, Nanning, Guangxi, 530007, China; Tel: +86-771-2503930; Fax: +86-771-2503999; E-mail: hongguanglishibahao@yahoo.com and 1968 [1], the highly pathological H5N1 outbreaks [2][3][4], and the current H1N1 pandemic [5][6][7]. Among ten proteins from influenza A viruses, we have studied this question with respect to the hemagglutinin, neuraminidase, polymerase acidic protein, matrix protein 1 and 2 [8][9][10][11][12], which bioinformatically reveal the underlined mechanism for the crossspecies infection and cross-subtype reassortment.…”
Section: Introductionmentioning
confidence: 99%
“…Seven different genotypes were detected among the 31 H5N1 isolates, including three not previously detected in humans ( Fig. 2 and 4; see Table S3 To identify potential avian virus gene precursors of each human isolate, we applied the CCV-MST method (1,22,23). One or more gene segments for most of the human H5N1 viruses isolated before 2007 had a corresponding gene segment in the public influenza database that was isolated from birds.…”
Section: Human H5n1 Cases In Chinamentioning
confidence: 99%
“…Ideally, we would compare the output of such an analysis with the systematic review, to understand both detection and publication biases. However, to our knowledge, existing phylogenetic algorithms appear to have low sensitivity (since the number detected is much lower than found by our systematic review) [ 20 , 24 , 26 , 27 ], and the most robust algorithms would be difficult to apply to all available data, since they rely on assumptions of analysing random representative samples and are computationally expensive to apply to very large datasets [ 21 ].…”
Section: Discussionmentioning
confidence: 99%